Pustula junggarensis (Albuginales, Oomycota), a new species of white blister rust on Takhtajaniantha pusilla from Junggar Basin in China - Xu, Biao; Song, Jiage Ge; Xi, Ping Gen; Jiang, Zi De (Phytotaxa, 2016)
An unknown white blister rust was collected on Takhtajaniantha pusilla (Pall.) Nazarovain (Asteraceae) in the desert regions of Junggar Basin in China. The pathogen is characterized by depressed primary sporangia,subglobose secondary sporangia with annulus, yellowish to dark reddish-brown oospores, (45.4)54.6–65.4(68.5) µm in diameter, with inner walls on average up to 2.7 µm thick and outer wall on average up to 5.2 µm thick, which is obviously larger than in the morphologically similar P. obtusata and P. helianthicola. Phylogenetic analyses based on cox2 mtDNA sequences provided the evidence that this pathogen is separated from other species of Pustula and forms a distinct lineage. Therefore, we consider this pathogen as a new species of Pustula, described here as Pustula junggarensis.